Effect of Bifidobacterium animalis subsp. lactis SF on enhancing the tumor suppression of irinotecan by regulating the intestinal flora. (October 2022) - Ren, Zhongyue; Chen, Shufang; Lv, Huihui; Peng, Lingling; Yang, Wanyu; Chen, Jiahui; Wu, Zhihua; Wan, Cuixiang
Abstract: The gut microbiota plays a role in tumor therapy by participating in immune regulation. Here, we demonstrated through 8-day probiotic supplementation experiments and fecal microbiota transplantation experiments that Bifidobacterium animalis subsp. lactis SF enhanced the antitumor effect of irinotecan and prevented the occurrence of intestinal damage by modulating the gut microbiota and reducing the relative abundance of pro-inflammatory microbiota. Therefore, the intestinal inflammation was inhibited, the TGF-β leakage was reduced, and the PI3K/AKT pathway activation was inhibited. Thus, the tumor apoptotic autophagy was finally promoted. Simultaneously, the reduction of TGF-β relieved the immunosuppression caused by CPT-11, promoted the differentiation of CD4 + and CD8 + T cells in tumor tissue, and consequently inhibited tumor growth and invasion. This study disclosed the mechanism of B. lactis SF assisting CPT-11 in antitumor activity and suggested that B. lactis SF plays a new role in anticancer effects as a nutritional intervention. Graphical Abstract: ga1